Formação do conceito de volume nos anos iniciais do ensino fundamental: Um experimento didático formativo baseado na perspectiva da Teoria do ensino desenvolvimental - De Freitas Vaz, Duelci Aparecido [UNESP]; Pereira, Natália Cristina Souza (My University, 2017)
We reflected about a research from the elaboration and application of a formative didactic experiment based on Davydov's Theory of Developmental Teaching (1978; 2009), composed of a comic book created in the Hagáquê software and three built activities and relating to the question that guided this study: Can an education organized on the basis of the Theory of Developmental Teaching contribute to the formation of the concept of cube volume, the parallelepiped, and the pyramid for students in the 5th year of Elementary Education? We used the qualitative and participatory methodology, in which the researcher interacted with the members of the investigated situations conceived as subjects of knowledge and not subjects of research, in the passive sense of data providers. Data analysis - obtained from observations, questionnaires, filming, and field annotations - was carried out in the light of the Theory of Developmental Teaching. The difficulties to carry out the research were related to the school supply conditions, such as inadequacy of the physical space, unavailability of computer lab, and the delay in the release of students. They undoubtedly hindered the development of the experiment, whose analysis shows that the organization of activities from a developmental perspective enables maturation and cognitive development of the student due to experiential experimentation, which enables the students to understand the nuclear aspect of the concept of volume of objects studied. The analysis also indicated that similar researches are promising, since the outstanding theoretical contribution caused changes in the scientific conception of the student and in the methodology of the teacher researcher professor.
Formation of the concept of volume in the early years of school: A formative teaching experiment based on the perspective of the Theory of developmental education
Keywords: Concept formation; Developmental education; Math club